2005
DOI: 10.1074/jbc.m411884200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Novel Vitamin B12 (Cobalamin) Biosynthetic Enzyme (CobZ) from Rhodobacter capsulatus, Containing Flavin, Heme, and Fe-S Cofactors

Abstract: One of the most intriguing steps during cobalamin (vitamin B 12 ) biosynthesis is the ring contraction process that leads to the extrusion of one of the integral macrocyclic carbon atoms from the tetrapyrrole-derived framework. The aerobic cobalamin pathway requires the action of a monooxygenase called CobG (precorrin-3B synthase), which generates a hydroxylactone intermediate that is subsequently ring-contracted by CobJ. However, in the photosynthetic bacterium Rhodobacter capsulatus, which harbors an aerobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 35 publications
1
53
0
Order By: Relevance
“…For example, we identified only two genes for cobalamin (vitamin B12) biosynthesis, cobalamin adenosyltransferase, and precorrin-3B synthetase (cobZ). CobZ has only been reported previously in bacteria and is a key enzyme in a poorly understood cobalamin biosynthetic pathway in photosynthetic bacteria (33). Searches of the UBA-BS and UBA datasets revealed that this is the only CobZ in either community.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we identified only two genes for cobalamin (vitamin B12) biosynthesis, cobalamin adenosyltransferase, and precorrin-3B synthetase (cobZ). CobZ has only been reported previously in bacteria and is a key enzyme in a poorly understood cobalamin biosynthetic pathway in photosynthetic bacteria (33). Searches of the UBA-BS and UBA datasets revealed that this is the only CobZ in either community.…”
Section: Resultsmentioning
confidence: 99%
“…In both cases it was envisaged that iron would be added at the final stage, as is observed with siroheme and the classic heme pathway. To test the hypothesis that heme d 1 synthesis may proceed via sirohydrochlorin, cell-free extracts of Escherichia coli, overproducing either individual P. pantotrophus Nir proteins (D-L, G, H, J, F) or combinations of them generated using our link and lock technology (18), were incubated with this metal-free substrate. Strikingly, when lysates of E. coli, overproducing P. pantotrophus NirDL-G-H, were incubated with sirohydrochlorin an instant change in the appearance of the purple sirohydrochlorin to a blue-green color was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmids containing nirED-L, nirGH, and nirD-LGH were constructed by inserting the appropriate amplified P. pantotrophus genes into pET3a using the link and lock method described in ref. 18. The nirH was cloned into pET14b, and thus the recombinant protein contained an N-terminal hexahistidine tag, whereas nirG and nirD-L were cloned into pET3a and pASKIBA13 plus vectors, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…CobZ was identified in Rhodobacter capsulatus, which catalyzes a reaction similar to that advanced by CobG, but in a different way, as the two proteins did not display any primary sequence resemblance. CobZ was also found to have a flavin in the form of a non-covalently bound FAD, two Fe-S centers, and a b-type heme, which was not similar to CobG [51]. It was thought that the final step in the cobalamin biosynthetic pathway in S. typhimurium involved the dephosphorylation of adenosylcobalamin-5′-phosphate, which is catalyzed by CobC and challenges the pathway indicated where CobS catalyzes the condensation of a-ribazole and an Ado-GDP-cobinamide [52].…”
Section: Vitamin B12 Biosynthesismentioning
confidence: 99%